Pharmacology and rationale for imatinib in the treatment of scleroderma - Moinzadeh P; Hunzelmann N; Krieg T (Dove Medical Press, 2013)
Pia Moinzadeh, Nicolas Hunzelmann, Thomas Krieg Department of Dermatology and Venerology, University of Cologne, Germany Abstract: Systemic sclerosis (scleroderma) is a chronic, multisystem, fibrotic disease. Although the pathogenesis is not completely understood, early vascular damage leads to an inflammatory reaction and a severe fibrotic response. Therapy of systemic sclerosis is still not convincing and is mainly restricted to the management of organ complications. A wide choice of immunosuppressive and antifibrotic drugs has been used to try to modify the course of the disease, but significant breakthroughs are still lacking. Imatinib is a tyrosine kinase inhibitor known to regulate growth, proliferation, and differentiation as well as apoptosis of cells and is already widely used for several malignancies, eg, chronic myeloid leukemia and gastrointestinal stromal tumors. It has been used in preclinical as well as clinical studies to modulate the fibrotic process in patients with systemic sclerosis. This is based on its activity to interfere selectively with both the transforming growth factor-ß and platelet-derived growth factor signaling pathway. Preclinical studies in mouse models of scleroderma showed significant anti-inflammatory and antifibrotic effects; however, several clinical, proof-of-concept trials have not yet confirmed these initially promising results. Keywords: scleroderma, systemic sclerosis, SSc, tyrosine kinase inhibitor, imatinib